Review of Metal-Organic Frameworks (MOFs) in Electronic Strain Skin (Journal of science and technology exploration, 2025)
With the continuous development of flexible electronic technology, electronic strain skin, as an important component that mimics human skin's ability to perceive external strains, has attracted increasing attention. Metal-organic framework (MOF) materials are particularly distinctive for electronic strain skin due to their tunable porous structure, high specific surface area, excellent flexibility, and chemical stability. This paper summarizes the latest applications of MOF materials in flexible strain sensors, focusing on their roles in enhancing sensor sensitivity, response speed, and cyclic stability. By rationally designing the structure and composition of MOFs to improve the signal conversion performance and mechanical durability of electronic skin, they can play a significant role in various fields such as health monitoring, human-computer interaction, and soft robotics. Although remarkable achievements have been made in current research, challenges still exist in aspects like large-scale material preparation, environmental adaptability, and long-term stability. Future research should continue to explore methods for improving the interface between MOFs and flexible substrates, and develop novel composite structures, thereby expanding the potential of their applications in multifunctional electronic skin.